Juridical Analysis of Lease Object Conversion in Lease Agreements for Shop-Houses in Tangerang Regency - Tjandraningsih, Dewi (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This study aims to analyze the implementation of lease object conversion in lease agreements for shop-houses in Tangerang Regency and the legal consequences arising from such conversion. The research uses an empirical juridical approach, employing primary and secondary data collected through interviews and literature reviews. The findings indicate the following: (1) Tenants intending to repurpose or convert the use of leased shop-house objects must inform the lessor (property owner) of their intention and obtain written consent. It is recommended that both parties draft an addendum to amend the existing lease agreement to reflect the new purpose. (2) If tenants fail to inform the lessor and obtain consent for the conversion, the lease agreement may be subject to termination.